Assessment of Gastrointestinal Parasites and Productive Parameters on Sheep Fed on a Ration Supplemented with Guazuma ulmifolia Leaves in Southern Mexico - Emelyne Le Bodo; Jean-Luc Hornick; Nassim Moula; Serrano Aracely Zuñiga; Juan Carlos Martínez-Alfaro (Animals, 2020)
This study aimed at evaluating the impact of a diet supplemented with Guazuma ulmifolia leaves on the productive performance and gastrointestinal parasites (GI) eggs/oocysts shedding of sheep (Pelibuey breed). Twenty-two non-lactating ewes were used. They were randomly allocated to two similar groups in terms of age, weight, body condition score (BCS), and GI parasites status. For 30 days, while the control group (G0) was given basic forage hay of Cynodon nlemfuensis, the test group (G1) received a blend of G. ulmifolia fresh foliage and C. nlemfuensis hay (respectively 30 and 70% of the diet on a DM basis). Animals were housed in separate covered pens. Quantitative coprological analysis was performed. Weight and BCS were evaluated. The daily feed amounts given and refused were measured in order to assess nutrient components intake (minerals, energy, and nitrogen). The results showed no significant differences between G1 and G0 regarding the anthelmintic and anticoccidial effects (p = 0.57, p = 0.91, respectively). Similarly, no significant overall impact on weight and BCS during the experiment (p = 0.77, p = 0.32, respectively) was observed. Nevertheless, concerning the bromatological analysis of G. ulmifolia, its use as a diet supplement to address protein and mineral deficits due to a poor-quality diet is fully justified.